Clinical Outcome of Third-Line Pazopanib in a Patient with Metastatic Renal Cell Carcinoma - Michela Roberto; Maria Bassanelli; Elsa Iannicelli; Silvana Giacinti; Chiara D’Antonio; Anna Maria Aschelter; Paolo Marchetti (Case Reports in Oncological Medicine)
Background. Renal cell carcinoma accounts for about 2-3% of all malignant tumors. The prevalence of brain metastases from RCC is less than 20% of cases. Traditionally, whole brain radiotherapy as well as the latest stereotactic radiosurgery improves both survival and local tumor control. These treatments also allow stabilization of clinical symptomatology. However, validated treatment guidelines for RCC patients with brain metastases are not yet available on account of the frequent exclusion of such patients from clinical trials. Moreover, limited data about the sequential use of three therapies, changing the class of agent, have been published up to now. Case Report. We report the case of a patient with metastatic RCC who developed disease progression after sunitinib and everolimus as first-line and second-line therapy, respectively. Thus, he underwent a multimodality treatment with pazopanib, as third-line therapy, to control systemic disease and radiosurgery directed on the new brain metastasis. To date, the patient is still receiving pazopanib, with progression-free survival and overall survival of 43 and 103 months, respectively. Conclusion. In a context characterized by different emerging options, with no general consensus on the optimal treatment strategy, the use of pazopanib in pretreated patients could be a suitable choice.